2021
DOI: 10.1111/his.14531
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression and morphological patterns in prostatic adenocarcinoma

Abstract: Aims Cribriform morphology, which includes intraductal carcinoma (IDCP) and invasive cribriform carcinoma, is an indicator of poor prognosis in prostate cancer. Phosphatase and tensin homologue (PTEN) loss is a predictor of adverse clinical outcomes. The association between PTEN expression and morphological patterns of prostate cancer is unclear. Methods and results We explored the association between PTEN expression by immunohistochemistry, Gleason pattern 4 morphologies, IDCP and biochemical recurrence (BCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
(92 reference statements)
1
23
1
Order By: Relevance
“…Besides the above-mentioned study by Risbringer et al [121], few groups have addressed the molecular features underlying the aggressivity of IDC-P [30,[128][129][130] (Table 5). Increasing our knowledge in this field will be central to the development of new therapies for men with IDC-P.…”
Section: Idc-p and Its Impact On Pca Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned study by Risbringer et al [121], few groups have addressed the molecular features underlying the aggressivity of IDC-P [30,[128][129][130] (Table 5). Increasing our knowledge in this field will be central to the development of new therapies for men with IDC-P.…”
Section: Idc-p and Its Impact On Pca Outcomementioning
confidence: 99%
“…Very recently, Spieker et al [130] identified PTEN loss in 86% of IDC-P cases (30/35 RPs) and in 64% of CC lesions (72/112 RPs). In this study, CC was associated with shorter time to biochemical recurrence (multivariate HR: 3.50, 95% CI: 1.89-6.49, p < 0.001) but not IDC-P alone.…”
Section: Idc-p and Its Impact On Pca Outcomementioning
confidence: 99%
“…Both entities can show a cribriform pattern of growth, and although they often coexist, studies have shown that there are concrete differences between the two. 6,7 Separating IDCP from invasive cribriform cancer often requires immunohistochemistry to determine the presence of basal cells, which would be seen in IDCP. Staining for the presence of basal cells in all areas of a tumor with cribriform morphology to distinguish IDCP from invasive cribriform cancer is both time-consuming and has additional costs.…”
mentioning
confidence: 99%
“…This may be problematic, as some studies have shown a difference in prognosis when separating the two. 7,8,9 A study by Spieker et al showed that a combination of IDCP and invasive cribriform cancer was an independent prognostic indicator for biochemical recurrence. 7 However, when splitting the two entities, only invasive cribriform cancer remained statistically significant, while IDCP did not.…”
mentioning
confidence: 99%
See 1 more Smart Citation